PERIODIZATION OF THE BOLIVIAN PLURINATIONAL CONSTITUTIVE MOMENT: AN AGRO-ENVIRONMENTAL VISION - Ponce de León Iturry, Juan Carlos (Revista de Historia Social y de las Mentalidades, 2022)
The hegemonic system in Bolivia between 2006 and 2019 reflects the deconstruction of the republican State and the erection of the plurinational State that seeks to establish itself beyond a reforming and progressive cycle, in an organic superstructure of ideological power and state bureaucracy. From an agro-environmental perspective, three moments of political analysis are presented, addressing the formal dimension of the discourse that describes the vision of the regime in function of government. To this end, the emergence of a political discourse supported by the plurinational constitutional text that aims to modify the matrix of thought through a significant, representative, and sufficiently homogeneous legal framework based on the mass of documents produced is exposed. The analysis developed exposes from the formal perspective how the regime in government, in the study period, intends to show the distance from republican ideas and the establishment of a harmonic environmental paradigm of development but that in a dialectical turn takes up the questioned republican practices.